Fatal Sarcocystis cruzi–induced eosinophilic myocarditis in a heifer in Uruguay - Aráoz, Virginia (2019)
Sarcocystis spp. are causative agents of bovine eosinophilic myositis and/or myocarditis, which are chronic subclinical myopathies that are occasionally responsible for condemnation at slaughterhouses. Sarcocystis cruzi is a protozoan parasite of worldwide distribution transmitted by canids, most commonly associated with subclinical infection in cattle. Although S. cruzi infections can rarely lead to fatal systemic disease, fatal cardiac cases with confirmation of the etiologic diagnosis have not been reported, to our knowledge. We describe herein an unusual case of S. cruzi–induced fatal bovine eosinophilic myocarditis. A 22-mo-old, Holstein–Hereford heifer, in a group of 110 cattle on pasture, manifested growth retardation and died in February 2017. Autopsy revealed myriad yellow-green 1–3-mm coalescing foci, surrounded by fibrosis, affecting ~75% of the ventricular myocardium. Pulmonary edema, ascites, and hydrothorax were consistent with chronic congestive heart failure. Histology revealed severe eosinophilic, granulomatous, necrotizing myocarditis, with multinucleate giant cells, fibrosis, and mineralization. Numerous thin-walled protozoan cysts resembling Sarcocystis spp. were present in the necrotic foci and within the sarcoplasm of adjacent cardiomyocytes. PCR and sequencing of the 18S rRNA gene revealed 99.9–100% homology with S. cruzi. Sarcocystosis can be a rare cause of fatal myocarditis in cattle.